World catalogue of the genus Cossulus Staudinger, 1887 (Lepidoptera, Cossidae) with description of Cossulus irtlachi sp. nov. from Kyrgyzstan - Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2017)
An annotated catalogue for the genus Cossulus Staudinger, 1887 including illustrations of adults and distribution maps is given. Data on the type material, synonymy, and distribution are provided for all the species. Cossulus irtlachi Yakovlev & Witt sp. nov. from Kyrgyzstan (Toktogul Reservoir) is described.